New strategies in HER2-overexpressing breast cancer: Many combinations of targeted drugs available - Abramson, Vandana (2011)
The anti-HER2 drugs trastuzumab and lapatinib are increasingly changing the natural history of early and metastatic HER2-overexpressing breast cancer. Many other agents targeted against the HER2 signaling network are in clinical development. These are or will soon be combined with the currently approved anti-HER2 therapies. We review herein recent data in support of the early use of combinations of agents targeted to the HER2 network as the most rational approach against this subtype of breast cancer. We propose the optimal combination or combinations of anti-HER2 agents delivered early in the natural history of HER2+ breast cancer should close to eliminate acquired drug resistance, shorten the duration of therapy, and potentially dispense with the need of concurrent chemotherapy.